Functional Near-Infrared Fluorescence Imaging for Cardiac Surgery and Targeted Gene Therapy - Akira Nakayama; Federica del Monte; Roger J. Hajjar; John V. Frangioni (Molecular Imaging)
Cardiac revascularization is presently performed without realtime visual assessment of myocardial blood flow or perfusion. Moreover, gene therapy of the heart cannot, at present, be directed to specific territories at risk for myocardial infarction. We have developed a surgical imaging system that exploits the low autofluorescence, deep tissue penetration, low tissue scatter, and invisibility of near-infrared (NIR) fluorescent light. By completely isolating visible and NIR light paths, one is able to visualize, simultaneously, the anatomy and/or function of the heart, or any desired tissue. In rat model systems, we demonstrate that the heptamethine indocyanine-type NIR fluorophores IR-786 and the carboxylic acid form of IRDye78 can be injected intravenously in the living animal to provide real-time visual assessment of myocardial blood flow or perfusion intraoperatively. This imaging system may prove useful for the refinement of revascularization techniques, and for the administration of cardiac gene therapy.